Clinical outcomes of flap reconstruction following lower extremity soft tissue sarcoma resection: a single-center retrospective experience - Xinxin Guo; Jianpeng Li; Jingyu Zhang; Yongcheng Hu (Frontiers in Surgery, 2026)
Background Soft tissue sarcomas (STSs) represent a diverse category of tumors with a propensity for the lower limbs. Wide surgical resection is the primary therapeutic approach, often requiring immediate flap reconstruction with or without perioperative adjuvant therapy. This study aims to share our clinical experience and assess the efficacy of customized flap reconstruction designed according to the precise defect area after lower extremity STS resection. Methods This retrospective analysis reviewed 15 cases of lower extremity STS with a median follow-up of 28.5 months (range: 8–58 months), where patients underwent flap reconstruction with or without adjuvant therapy at our institution. Owing to the small cohort size, analyses were primarily descriptive. Continuous variables were summarized as the median, interquartile range, and range, whereas categorical variables were reported as frequencies and percentages. Exact 95% confidence intervals were calculated for selected proportions. Results The cohort comprised 7 male (46.7%) and 8 female (53.3%) patients, with a median age of 65.0 years (IQR, 52.0–76.8 years; range, 31–86 years). All patients achieved microscopic negative margins (R0 resection), and 10 (66.7%) received adjuvant therapy. The median flap surface area was 120 cm² (IQR, 80–171 cm 2 ; range, 42–240 cm 2 ). Five patients developed postoperative complications—including partial flap necrosis, delayed donor- or graft-site healing, infected sinus tract formation, and hematoma—yielding a complication rate of 33.3% (exact 95% CI, 11.8%–61.6%). Complete wound closure was eventually achieved in all cases. Over the follow-up period, five deaths (four disease-related) and four cases of disease progression were documented. Conclusion In this single-center retrospective series, flap-based reconstruction was a feasible limb-salvage strategy after lower extremity STS resection, providing reliable coverage for complex defects. Although postoperative complications occurred in some patients, flap reconstruction remained an important component of multidisciplinary limb-preservation treatment, particularly when combined with careful perioperative management.